Suppression of inner ear signal intensity on fluid-attenuated inversion recovery magnetic resonance imaging in cats with vestibular disease. Issue 4 (April 2023) - Everest, Stephen; Monteith, Gabrielle; Gaitero, Luis; Samarani, Francesca
Objectives: Otitis media/interna (OMI) is the most common cause of peripheral vestibular disease in cats. The inner ear contains endolymph and perilymph, with perilymph being very similar in composition to cerebrospinal fluid (CSF). As a very-low-protein fluid, it would be expected that normal perilymph should suppress on fluid-attenuated inversion recovery (FLAIR) MRI sequences. Based on this, we hypothesized that MRI FLAIR sequences should provide a non-invasive way of diagnosing inflammatory/infectious diseases such as OMI in cats, something that has previously been demonstrated in humans and, more recently, in dogs. Methods: This was a retrospective cohort study in which 41 cats met the inclusion criteria. They were placed into one of four groups, based on presenting complaint: clinical OMI (group A); inflammatory central nervous system (CNS) disease (group B); non-inflammatory structural disease (group C); and normal brain MRI (control group; group D). Transverse T2-weighted and FLAIR MRI sequences at the level of the inner ears bilaterally were compared in each group. The inner ear was selected as a region of interest using Horos, with a FLAIR suppression ratio calculated to account for variability in signal intensity between MRIs. This FLAIR suppression ratio was then compared between groups. Statistical analyses were performed by an experienced statistician, with a general linear model used to compare mean FLAIR suppression ratio, CSF nucleated cell count and CSF protein concentration between groups. Results: The OMI group (group A) had significantly lower FLAIR suppression scores compared with all other groups. The CSF cell count was also significantly increased in the OMI (group A) and inflammatory CNS disease (group B) groups compared with the control group (group D). Conclusions and relevance: This study demonstrates the utility of MRI FLAIR sequences in diagnosing presumptive OMI in cats, similarly to in humans and dogs. This study is relevant to practicing veterinary neurologists and radiologists in interpreting MRI findings in cats with suspected OMI.